2022
DOI: 10.1098/rsos.202136
|View full text |Cite
|
Sign up to set email alerts
|

Strategies that reduce Stroop interference

Abstract: A remarkable example of reducing Stroop interference is provided by the word blindness post-hypnotic suggestion (a suggestion to see words as meaningless during the Stroop task). This suggestion has been repeatedly demonstrated to halve Stroop interference when it is given to highly hypnotizable people. In order to explore how highly hypnotizable individuals manage to reduce Stroop interference when they respond to the word blindness suggestion, we tested four candidate strategies in two experiments outside of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Similarly, in the current AC tasks, participants could have been motivated to utilize different task strategies to reduce conflict and enhance performance. For example, prior research on the Stroop suggests participants utilize various strategies to reduce the conflict between color and word (e.g., Palfi et al, 2022; Sheehan et al, 1988). These include various visual strategies such as looking away from the word, visual blurring to reduce word reading, and focusing on a single letter (e.g., Palfi et al, 2022; Sheehan et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in the current AC tasks, participants could have been motivated to utilize different task strategies to reduce conflict and enhance performance. For example, prior research on the Stroop suggests participants utilize various strategies to reduce the conflict between color and word (e.g., Palfi et al, 2022; Sheehan et al, 1988). These include various visual strategies such as looking away from the word, visual blurring to reduce word reading, and focusing on a single letter (e.g., Palfi et al, 2022; Sheehan et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For example, prior research on the Stroop suggests participants utilize various strategies to reduce the conflict between color and word (e.g., Palfi et al, 2022; Sheehan et al, 1988). These include various visual strategies such as looking away from the word, visual blurring to reduce word reading, and focusing on a single letter (e.g., Palfi et al, 2022; Sheehan et al, 1988). Another strategy is to simply repeat the task goal (“color”) in order to aid active goal maintenance (e.g., Hood & Hutchison, 2021; Palfi et al, 2022; Sheehan et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Irons and Leber (2020) have argued that people use dramatically different cognitive strategies for controlling attention, and that there is evidence to suggest that optimal strategy use is unrelated to general cognitive ability. Similarly, studies have shown that cognitive control strategies can have a marked effect on performance when performing Stroop-like tasks (Palfi et al, 2022;Starodubtsev & Allakhverdov, 2021) and on other conflict tasks (Hedge et al, 2021). Clarke et al (2022) also recently showed that participants strategies on a particular visual search task were stable over time, suggesting that, after finding a strategy, participants will not tend to try new strategies unless instructed to do so.…”
Section: Cognitive Controlmentioning
confidence: 95%
“…Psychometrics, or the study of individual differences, is a foreign country to many experimental psychologists. The wildest dream of any researcher working in the experimental tradition is to develop a paradigm like the Stroop task: Everyone stroops and participants can't do much to suppress the effect, even if they want to (Palfi et al, 2022). Experimenters working with such tasks can rest assured that they will never fail to reproduce the basic within-participants effect, even with small samples and adverse experimental conditions (Zwaan et al, 2018).…”
mentioning
confidence: 99%